Healthy building standards, their integration into green building practices and rating systems for one health - Stahel Serano Bibang Bi Obam Assoumou; Li Zhu; Christopher Khayeka-Wandabwa (Discover Sustainability)
Abstract Globally, the built-up areas are witnessing notable exponential growth prompting ecological and ecosystem services shifts. The trajectory is in tune with the increasing recognition that social determinants of health (conditions in which people are born, grow, work, live, worship, and age) affect human health and well-being. As green building (GB) concepts advance globally and people spend more time indoors, both developers and end users have prioritized more thoughtful spaces that promote human health, well-being, and resource efficiency throughout their entire life cycle. The scoping review examines the evolving trends of healthy building standards and their integration into the green building and green building rating system (GBRS) along with how the advances interlink to health and well-being. Twenty-seven studies were included in the review with a focus on green building, GBRS, healthy building, and healthy building standards. Prevailing GBRS for evaluation of green buildings emphasizes indoor environmental quality (IEQ) and indoor air quality (IAQ) with limited incorporation of health attributes notably, WELL standards. There is a compelling need to synchronize green building and rating systems with healthy building standards and rating systems measures to uphold the physical, psychological, and physiological health of a built environment and its occupants at one go in the project cycle. Thus, GBRS for GB ought to prioritize the WELL concept and the interdisciplinary intersections tradeoffs with priority on the lags in nourishment, movement, mind, and community given one health and globalization interplays. The interplays would entail but not be limited to evolving socio-cultural influences (like shared workspace, remote working, and teleworking perception post-COVID-19 pandemic), enabling intelligent technologies among other ecosystem services.